The impact of FinTech on bank's credit risk: Evidence from China - Wu, Danzi (2022)
The effects of fintech on bank credit risk are investigated using a quantitative study design (panel regression with fixed effect) in this work. For starters, this article uses the financial data of 42 Chinese listed banks from 2007 through 2021 to build a credit risk indicator. The total number of fintech-related terms appearing in the annual reports released by these banks throughout the same time period was then used to generate the fintech indicators. Empirical study results in this paper reveal that FinTech raises banks' credit risk after controlling for macroeconomic and bank-level factors, but has no effect on the credit risk of state-owned banks.